Glaucoma screening in Kazakhstan - Malika Urazhanova; Elvira Kadraliyeva; Zhibek Dautbayeva; Yuliya Semenova (Scientific Reports)
Abstract This study aimed to conduct a comprehensive analysis of the national glaucoma screening program in Kazakhstan from 2000 to 2022. A thorough search was conducted to identify policy documents regulating the provision of glaucoma screening from its inception to the present day. Official data on reimbursement for tonometry, glaucoma incidence, and the population aged ≥ 50 years were retrieved. Forecast modeling was utilized to project disease incidences up to 2030. The current program largely inherits the framework of the Soviet glaucoma screening, with tonometry serving as the primary screening tool. The budget allocated for glaucoma screening is not specified in official documents, as glaucoma screening is integrated into the routine activities of healthcare facilities. The highest costs are incurred when Maklakov tonometry is applied alone, reaching 7,557,679,411 Kazakhstani Tenge in 2023. The incidence of glaucoma increased from 59.1 per 100,000 in 2000 to 135.5 in 2022, reflecting the aging population. Disparities in incidence rates were observed between residents of urban and rural areas, as well as among residents of different provinces. It is anticipated that the incidence of glaucoma will continue to rise, reaching 154.5 per 100,000 in 2030. There is a need to initiate a discussion on potential amendments to the existing screening program.